Inflammatory Pathways Are Impaired in Alzheimer Disease and Differentially Associated With Apolipoprotein E Status. Issue 10 (6th September 2021) - Kloske, Courtney M; Dugan, Adam J; Weekman, Erica M; Winder, Zachary; Patel, Ela; Nelson, Peter T; Fardo, David W; Wilcock, Donna M
Abstract: Alzheimer disease (AD) is a neurodegenerative disease characterized by a cognitive decline leading to dementia. The most impactful genetic risk factor is apolipoprotein E (APOE). APOE-ε4 significantly increases AD risk, APOE-ε3 is the most common gene variant, and APOE-ε2 protects against AD. However, the underlying mechanisms of APOE-ε4 on AD risk remains unclear, with APOE-ε4 impacting many pathways. We investigated how the APOE isoforms associated with the neuroinflammatory state of the brain with and without AD pathology. Frozen brain tissue from the superior and middle temporal gyrus was analyzed from APOE-ε3/3 (n = 9) or APOE-ε4/4 (n = 10) participants with AD pathology and APOE-ε3/3 (n = 9) participants without AD pathology. We determined transcript levels of 757 inflammatory related genes using the NanoString Human Neuroinflammation Panel. We found significant pathways impaired in APOE-ε4/4-AD individuals compared to APOE-ε3/3-AD. Of interest, expression of genes related to microglial activation ( SALL1 ), motility ( FSCN 1), epigenetics ( DNMT1 ), and others showed altered expression. Additionally, we performed immunohistochemistry of P2RY12 to confirm reduced microglial activation. Our results suggest APOE-ε3 responds to AD pathology while potentially having a harmful long-term inflammatory response, while APOE-ε4 shows a weakened response to pathology. Overall, APOE isoforms appear to modulate the brain immune response to AD-type pathology.